2014
DOI: 10.1371/journal.pone.0107431
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Fraction of Bergamot Juice Reduces LPS-Induced Inflammatory Response through SIRT1-Mediated NF-κB Inhibition in THP-1 Monocytes

Abstract: Plant polyphenols exert anti-inflammatory activity through both anti-oxidant effects and modulation of pivotal pro-inflammatory genes. Recently, Citrus bergamia has been studied as a natural source of bioactive molecules with antioxidant activity, but few studies have focused on molecular mechanisms underlying their potential beneficial effects. Several findings have suggested that polyphenols could influence cellular function by acting as activators of SIRT1, a nuclear histone deacetylase, involved in the inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
92
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 41 publications
4
92
1
2
Order By: Relevance
“…Additionally, S100A4 induced an inflammatory response partially mediated by activation of NF-κB in mononuclear cells from patients with RA (43). on the contrary, bergamot juice can inhibit LPS-induced proinflammatory cytokines involved in the inhibition of NF-κB activation (40). In accordance with these studies, our data showed that S100A8 significantly activated the nF-κB pathway in macrophages in the inflammatory microenvironment and promoted both gene expression and secretion of inflammatory cytokines (IL-1β and TNF-α).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, S100A4 induced an inflammatory response partially mediated by activation of NF-κB in mononuclear cells from patients with RA (43). on the contrary, bergamot juice can inhibit LPS-induced proinflammatory cytokines involved in the inhibition of NF-κB activation (40). In accordance with these studies, our data showed that S100A8 significantly activated the nF-κB pathway in macrophages in the inflammatory microenvironment and promoted both gene expression and secretion of inflammatory cytokines (IL-1β and TNF-α).…”
Section: Discussionmentioning
confidence: 97%
“…It is well known that the nF-κB signaling pathway plays a crucial role in immune-regulation and inflammatory response via the induction of inflammatory cytokines (such as IL-6, IL-1β and TNF-α), cyclooxygenase-2 (CoX-2) and inducible nitric oxide synthase (inoS) (40). For instance, transcriptional activity of nF-κB may be most critical in S100A8/A9-induced expression of proinflammatory cytokines in monocytes/macrophages (41).…”
Section: Discussionmentioning
confidence: 99%
“…While this fruit is primarily used in the fragrance industry for its essential oil extracted from its peel, recent studies on the juice from the endocarp of bergamot have shown that it has several bioactivities such as antioxidant, antiinflammatory, cytotoxic, neuroprotective, as well as hypolipidemic and hypoglycemic properties (Currò et al 2016;Impellizzeri et al 2015;Miceli et al 2007;Mollace et al 2008;Risitano et al 2014;Sicari et al 2016;Trovato et al 2010;Tundis et al 2012). From clinical and mechanistic studies, it has been proposed (Mollace et al 2011) that melitidine and brutieridine in concert with naringin and other flavonone glycosides might be responsible for the hypolipidemic effects of BFE and function as do the statin drugs through the direct action on 3-hydroxy-3-methyl-glutaryl -coenzyme A (HMG-CoA) reductase activity.…”
Section: Introductionmentioning
confidence: 99%
“…LPS is a well-characterized inducer of inflammatory response and the pro-inflammatory activity of LPS-induced TLR4 expression plays an important role in pathological responses in autoimmune disorders and chronic inflammatory conditions, with the development of atherosclerosis, neurodegenerative diseases, and other chronic diseases [4]. Once activated, TLR4 initiates downstream signaling pathways [mitogen-activated protein kinases (MAPKs) and nuclear factor κB (NF-κB)], resulting in the release of cytokines such as interleukin (IL)-6, IL-1β, IL-8, IL-12p40, tumor necrosis factor (TNF)-α, IL-18, and NO, which then mediate the innate immune response and inflammatory response [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Monocytes are key cells of the innate immune system and are responsible for the initiation, progression and resolution of inflammation, pathogen clearance, wound healing, and tissue homeostasis [6,15]. THP-1 is widely used as a model to study inflammatory response.…”
Section: Introductionmentioning
confidence: 99%